Prospective multinational serosurveillance study of Bordetella pertussis infection among 10- to 18-year-old Asian children and adolescents. (February 2019) - Son, S.; Thamlikitkul, V.; Chokephaibulkit, K.; Perera, J.; Jayatilleke, K.; Hsueh, P.-R.; Lu, C.-Y.; Balaji, V.; Moriuchi, H.; Nakashima, Y.; Lu, M.; Yang, Y.; et al.
Abstract: Objectives: Bordetella pertussis continues to cause outbreaks worldwide. To assess the role of children and adolescent in transmission of pertussis in Asia, we performed a multinational serosurveillance study. Methods: From July 2013 to June 2016, individuals aged 10 to 18 years who had not received any pertussis-containing vaccine within the prior year were recruited in 10 centres in Asia. Serum anti–pertussis toxin (PT) IgG was measured by ELISA. Demographic data and medical histories were obtained. In the absence of pertussis immunization, anti-PT IgG ≥62.5 IU/mL was interpreted as B. pertussis infection within 12 months prior, among them levels ≥125 IU/mL were further identified as infection within 6 months. Results: A total of 1802 individuals were enrolled. Anti-PT IgG geometric mean concentration was 4.5, and 87 (4.8%) individuals had levels ≥62.5 IU/mL; among them, 73 (83.9%) had received three or more doses of pertussis vaccine before age 6 years. Of 30 participants with persistent cough during the past 6 months, one (3.3%) had level ≥125 IU/mL. There was no significant difference in proportions with anti-PT IgG ≥62.5 IU/mL among age groups (13–15 vs. 10–12 years, 16–18 vs. 10–12 years), between types of diphtheria, pertussis and tetanus (DTP; whole cell vs. acellular), number of doses before age 6 years within the DTP whole-cell pertussis vaccine (five vs. four doses) or acellular pertussis vaccine (five vs. four doses) and history of persistent cough during the past 6 months (yes vs. no). Conclusions: There is significant circulation of B. pertussis amongst Asian children and adolescents, with one in 20 having serologic evidence of recent infection regardless of vaccination background.